Evolutionary socialism : - Eduard Bernstein ; introd. by Sidney Hook ; [translated by Edith C. Harvey] (Schocken Books, 1963)
Translation of Die Voraussetzungen des Sozialismus und die Aufgaben der Sozialdemokratie.